2019
DOI: 10.1108/jcs-02-2019-0009
|View full text |Cite
|
Sign up to set email alerts
|

Participation as a methodological and ethical issue in child protection research

Abstract: Purpose The purpose of this paper is to explore how children have been involved in research activities in recent international child protection research and what kinds of ethical and methodological decisions are made by researchers regarding children’s participation. Design/methodology/approach In the paper, the complexity of children’s participation in research activities is analysed through an integrative literature review. Findings Children’s right to self-determination and the right to make informed de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 48 publications
(85 reference statements)
0
35
0
Order By: Relevance
“…In childhood and child welfare research, the criticism has been made that opportunities for child participation are all too often made available only to children judged to be capable of doing so by child welfare professionals and researchers (Kim, 2016;Kiili and Moilanen, 2019). In the context of service user involvement, this is a valid concern.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In childhood and child welfare research, the criticism has been made that opportunities for child participation are all too often made available only to children judged to be capable of doing so by child welfare professionals and researchers (Kim, 2016;Kiili and Moilanen, 2019). In the context of service user involvement, this is a valid concern.…”
Section: Discussionmentioning
confidence: 99%
“…Children were not considered to be partners in ethical reflection, despite the fact that children's needs, aspirations and realities should be at the core of service user involvement. Several studies have shown that effective service user participation involves encouraging and supporting children to express their views and challenge uncritical acceptance by authorities of the gatekeeping of their knowledge by professionals (Kiili and Moilanen, 2019;Tisdall, 2017;Jackson et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet Keats' work does not involve the (adult) participants in the analysis, and Nind (2011) notes that more research is needed on how learning-disabled children, in particular, can engage in data analysis. In a review of research with children in contact with child welfare services, of the 78 studies included, only four described how children were included in data analysis (Kiili et al, 2019). Subsequent research (Larkins et al, 2013;Gillet-Swan and Sargeant, 2018) has shown that narrative summaries of interviews and collaborative coding can enable children to add cultural and contextual insight in the analysis of data generated with other children and young people.…”
Section: A Review Of Stories As Researchmentioning
confidence: 99%